Tyramide Signal Amplification (TSA)-FISH Applied to Mapping PCR-Labeled Probes Less than 1 kb in Size. (September 1999) - Schriml, L.M.; Padilla-Nash, H.M.; Coleman, A.; Moen, P.; Nash, W.G.; Menninger, J.; Jones, G.; Ried, T.; Dean, M.
Tyramide signal amplification (TSA)-FISH was used to map one mouse and two human DNA probes of less than 1 kb in size. The two human probes were 319 and 608 bp, and the mouse probe was 855 bp. Probes, made from PCR products, were labeled by incorporating biotin-11-dUTP (human) and biotin-16-dUTP (mouse) during PCR amplification. Signals were readily observed in both interphase and metaphase cells following TSA-FISH for all three genes, whereas conventional FISH experiments produced no signals. The two human ATP-binding cassette (ABC) genes, EST883227 (GenBank ® Accession No. AA243820) and EST990006 (GenBank Accession No. AA348546), mapped to human chromosomes 7p21 and 17q25. The mouse gene, cmyc (exon 2) mapped to band D2 of mouse chromosome 15. These findings demonstrate the ability of this technique to map small probes (PCR products and expressed sequence tags) of less than 1 kb through highly increased signal amplification.